Tingkat Literasi Informasi Siswa MAN 1 Jembrana Menggunakan BIG 6 Model - Moch Syahri; Agus Musaddiq Fikri; Dwi Novita Ernaningsih (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2021)
This study aims to determine the level of information literacy of students in MAN 1 Jembrana. This research uses descriptive quantitative method. The population in this study were students of class XI MAN 1 Jembrana with a total of 200 people. Sampling in this study was 10% using the random sampling method using the Slovin approach. The data collection technique used in this study is a closed questionnaire. The results show that the level of information literacy of students in MAN 1 Jembrana is included in the good category, by obtaining an overall average score of 3.15..